Reallocation and the Role of Firm Composition Effects on Aggregate Wage Dynamics - Effrosyni (Efi) Adamopoulou; Emmanuele Bobbio; Marta De Philippis; Federico Giorgi (Institute of Labor Economics (IZA), 2018)
Aggregate wages display little cyclicality compared to what a standard model would predict. Wage rigidities are an obvious candidate but a recent strand of the literature has emphasized the need to take into account the growing importance of worker composition effects during downturns. With reference to the Italian case we document that also firm composition effects increasingly matter in explaining the aggregate wage dynamics, i.e. aggregate wage growth has been lifted up by the increase in the employment weight of high wage firms. To the extent that this reallocation occurs towards more productive firms, the composition effects may also reflect an efficiency enhancing mechanism. We use a newly available dataset based on social security records covering the universe of Italian employers be-tween 1990 and 2013 and employ a standard measure of allocative efficiency on wages paid across firms. We show that this measure has improved over time since prior to the recent downturn and that it is aligned, at the sectoral level, with measures of productivity growth and market openness to competition. We then focus on the recent downturn and find that large firms were able to adjust wages more than small firms, and that small firms instead adjusted employment to a larger extent. Finally, we document that the continued improvement in the measure of allocative efficiency over this period correlates positively with measures of economic activity (evolution of employment and value added) across sectors.
Keywords: D61; E24; 330; aggregate wage dynamics; reallocation; allocative efficiency; firm composition effects